Stump Length and Its Role in Improving Functional Mobility Among Transtibial Prosthesis Users - Atika Febri Anggriani; Prasetyo Catur Utomo; Aprilia Rihhadatul ‘Aisy (Jurnal Keterapian Fisik, 2026)
Background: Transtibial amputations generally have a better survival prognosis, and the remaining stump length after transtibial amputation (ideally 12-35 cm) plays a crucial role in the functional mobility of prosthesis users, including balance, weight transfer, walking, and daily activities. Mobility limitations can negatively impact the social aspects, quality of life, and health of amputees, making restoring mobility through prosthesis use an important goal. The purpose of this study was to determine and prove to evaluate the contribution of stump length the relationship between stump length and functional mobility in transtibial prosthesis users.   Methods: The research method used was quantitative, with an analytical observational study and a cross-sectional design. A total of 15 respondents were selected from a population of 55 below-knee amputee patients using transtibial prostheses using a purposive sampling technique using the L – Test of Functional Mobility instrument.   Results: The Spearman Rank Correlation test produced a p-value of <0.001 which is statistically significant with a correlation coefficient of 0.845 which is very strong and positive. So, there is a very strong relationship between stump length and functional mobility in transtibial prosthesis users.   Conclusion: The longer the transtibial stump, the better the functional mobility. It is recommended that during amputation the stump be kept as long as possible.